PERAN ESTROGEN REMODELLING TULANG PADA KASUS OSTEOPOROSIS POST-MENOPAUSAL - Rizqa Inayati; Widani Darma Isasih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Osteoporosis is a bone disorder characterized by a decrease in bone density. One of the main factors causing osteoporosis is age. As a person ages, the prevalence rate of osteoporosis will increase, especially in women. The prevalence of osteoporosis is more common in elderly women. This is associated with the menopause. In menopause occurs decrease in estrogen hormone levels. The estrogen can protect bones from loss of bone mass through bone remodeling mechanisms. This literature review aims to know the role of estrogen on bone remodeling in post-menopusal osteoporosis. This literature review was carried out using Google Scholar, PubMed, and ResearchGate. The results of this literature review concluded that the estrogen has an important role in bone remodeling. The estrogen has anti-remodeling effect which can promote osteoclast apoptosis and induce osteoblast anti-apoptosis. Estrogen deficiency due to age in one of the factors that causes osteoporosis in post-menopausal osteoporosis.